Protective Effects of Mesenchymal Stem Cells Against Central Nervous System Injury in Heat Stroke - Yuan, Rui; Wang, Lu; Deng, Zi-Hui; Yang, Meng-Meng; Zhao, Yan; Hu, Jie; Zhang, Yu; Li, Yun; Liu, Meng; Liu, Shi-Fei; Zhou, Fei-Hu; Hanyu-Zhu; et al. (Current Stem Cell Research & Therapy, 2023)
Background: Heatstroke (HS) is a serious disease caused by central nervous system (CNS) injuries, such as delirium, convulsion, and coma. Currently, mesenchymal stem cells (MSCs) have demonstrated novel neuroprotective effects; therefore, this research explores the neuroprotective effects and mechanisms of MSCs against HS injury. Methods: HS rat models were induced in a 40°C and 65% humidity environment until the rectal temperature reached 42°C. The verified HS injury model rats were divided into the HS and MSCs-treated groups. Each rat in the treated group was infused with 1x106 MSCs suspended in 0.3 ml physiological saline via the tail vein. The HS- or MSCs-treated rats were further divided into early-stage (3d) and late-stage (28d). HS rat models were induced by a high-temperature and high-humidity environment at a specific time, the mortality was analyzed, and an automatic biochemical analyzer measured levels of liver and kidney function indicators in the blood. The neurons' morphologic changes were observed through Nissl staining, and neurological deficit scores were performed. Moreover, the levels of inflammatory factors in brain tissue were measured using a multi-cytokine detection platform, and the expression of BDNF, phosphorylated TrkB and P38 were detected by the Western Bolt. Results: MSCs injection significantly reduced mortality and alleviated liver and kidney function. Moreover, the neurological deficit and neuronic edema of the hippocampus caused by HS at 3d and 28d were significantly ameliorated by MSCs administration. Specifically, the injection of MSCs inhibited high levels of interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α), and IL-17A caused by HS but elevated the levels of IL-10 and IL-13 in the early period (3d); while in the later period (28d), MSCs significantly increased the levels of IL-10 and IL-13 continuously and inhibited the high level of IL-17A. Furthermore, MSCs injection increased the expressions of BDNF and phosphorylated TrkB (BDNF receptor), meanwhile inhibiting the expression of phosphorylated P38 (inflammatory factor) in the brains of HS rats in the early period (3d) but had no significant influence on the later period (28d). Conclusion: These results suggested that MSCs injection may provide therapeutic effects for HS in rats by improving liver and kidney function and reducing CNS damage. Moreover, MSCs injection inhibited the brain inflammatory response of HS rats, and the BDNF-TrkB and P38/MAPK signal pathways may be involved, providing a potential mechanism for HS therapy by MSCs administration.
Keywords: Heat stroke